Association of Dietary Practices and Lifestyle Modifications in Gastroesophageal Reflux Disease in Pakistani Women - Basharat, Shahnai; Ahsan, Fatima Binté; Zubair, Mehak; Chaughatta, Azka Ahmad; Mahmood, Ashna; Mahmood, Urva; Sheikh , Ahsan Sattar; Gillani, Syed Amir (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Background: Gastroesophageal Reflux Disease (GERD) incidence is increasing day by day due to lifestyle changes and living standards that resulted in esophagitis, esophageal adenocarcinoma, Barrett’s esophagus and many other illness worldwide. Patients with GERD live with poor quality life and have low work capacity. Aims: Main aim of the study is to diagnose GERD in early stages for the reduction in mortality and morbidity at different age groups. Methods: The pre-tested questionnaire was used to collect data from Sir Ganga Ram Hospital Lahore. A total of 230 female patients screened for GERD symptoms were included in this study. The collection of demographic data, dietary intake, lifestyle habits, physiology, and physical analysis were gathered during the 4 months. Results: Data analysis shows us that GERD is highly significant with age, occupation. Moreover, burping is highly significant in these patients. Fried fatty foods, spicy foods, fizzy drinks, garlic intake were also correlated to GERD symptoms. These subjects also suffer from more skin problems. Conclusion: From our results, we infer that GERD has a very strong bond with dietary and lifestyle patterns. If these parameters are kept under control, GERD patients will be less agonize from complications and minimize our morbidity and mortality.